Pengaruh Tingkat Pendidikan dan Pengalaman Kerja terhadap Kinerja Karyawan: Narrative Literature Review - Annisa Ika Deswanti; Yunita; Dewiana Novitasari; Masduki Asbari; Agus Purwanto (AGUSPATI RESEARCH INSTITUTA, 2023)
Performance development includes personality, experience, competence, and education, as well as behavior modification and improvement techniques, which provide added value that enables a person to work better. The resources owned by the company will not produce optimal results if they are not supported by human resources who have optimal performance. Efforts to improve employee performance include taking into account the level of education. In addition, work experience is also needed by employees to improve employee performance. The purpose of this study was to determine the effect of education level and work experience on employee performance. The research method this time is a quantitative research method presented in the form of a narrative literature review. The results of the study show that education and work experience have a good effect on employee performance so that companies pay attention to education and work experience because they have an influence on their performance and to achieve company goals. Keywords : Education, Work Experience, Performance